2021
DOI: 10.1002/chem.202005248
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Spin Density, Baird‐Antiaromaticity, and Singlet–Triplet Energy Gap in Triplet‐State Polybenzenoid Systems from Simple Structural Motifs

Abstract: Triplet‐state aromaticity has been recently proposed as a strategy for designing functional organic electronic compounds, many of which are polycyclic aromatic systems. However, in many cases, the aromatic nature of the triplet state cannot be easily predicted. Moreover, it is often unclear how specific structural manipulations affect the electronic properties of the excited‐state compounds. Herein, the relationship between the structure of polybenzenoid hydrocarbons (PBHs) and their spin‐density distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(68 citation statements)
references
References 113 publications
4
64
0
Order By: Relevance
“…Our ambition is to develop rened design rules based on aromaticity as this can facilitate the identication of novel ways for the tailoring of molecules that function as chromophores for singlet ssion photovoltaics. Aromaticity comes in different forms, e.g., Hückel-, 18 Möbius-, 19,20 Baird-, [17][18][19][20][21][22][23][24][25][26][27][28][29] and spherical aromaticity. 30,31 Of relevance for the study presented herein are Hückel-aromaticity of closed-shell cycles with 4n + 2p-electrons and Baird-aromaticity of cycles with 4np-electrons in their triplet pp* states.…”
Section: Introductionmentioning
confidence: 99%
“…Our ambition is to develop rened design rules based on aromaticity as this can facilitate the identication of novel ways for the tailoring of molecules that function as chromophores for singlet ssion photovoltaics. Aromaticity comes in different forms, e.g., Hückel-, 18 Möbius-, 19,20 Baird-, [17][18][19][20][21][22][23][24][25][26][27][28][29] and spherical aromaticity. 30,31 Of relevance for the study presented herein are Hückel-aromaticity of closed-shell cycles with 4n + 2p-electrons and Baird-aromaticity of cycles with 4np-electrons in their triplet pp* states.…”
Section: Introductionmentioning
confidence: 99%
“…We pass to anthracene which mainly localizes triplet state antiaromaticity to the middle ring (NICS scans in Figures 2 and S1, the AICD plot in Figure S12, HOMA middle ring =0.494, EDDB F(middle ring) =2.493 e and EDDB F(α‐β) /EDDB F =0.160) having the highest spin density (Figure 1). We note that a detalied analysis of spin density distribution in polybenzenoid compounds and its relation to antiaromaticity was published recently [61] . The authors of this reference showed that spin localization on a specific subunit(s) allowed the remaining ones to recover their aromaticity.…”
Section: Resultsmentioning
confidence: 87%
“…This resembles the ground state properties of (poly)benzenoid compounds. • Substitution at α‐position of an outer ring creates more aromatic subunit than substitution at β‐position (substitution at the ring‐junction position only decreases antiaromaticity). There is no difference between the two different α‐positions, as, for example, in phenanthrene. • Two silicon atoms in 1,4‐position within one ring allow the formation of more aromatic carbocyclic subunits than one silicon atom, due to better unpaired electrons′ localization. • Though the extent of aromaticity of carbocyclic subunits of the same type appears as more pronounced in angular vs linear geometry and for synperiplanar (sp) vs antiperiplanar (ap) arrangement of the Si−H bonds in disilicon‐containing compounds, the difference is small. • Two isomeric carbocyclic subunits are equally efficiently created by putting the silicon atom(s) into various α‐positions of outer benzene rings within a polycycle. These results show that the spin localization in PAHs on particular subunit(s), enabling recovery of Hückel aromaticity of the others, [61] can be shifted to different rings by the silicon substitution allowing the fine tuning of S 0 −T 1 energy gaps, which nicely correlate with the extent of global aromaticity represented by ISE values (Figure S37f, R 2= 0.769). Formation of wings‐shaped sp structure upon excitation of the planar disila‐compound may be interesting for developing of photomechanical materials, featuring a kind of movement (change of shape) as a response to light. Having known that silicon substituted (poly)benzenoid compounds have been synthesized, we hope that the rules established in this work can be useful in future design of organic compounds‐based materials.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations